Stability Analysis Of Islamic Banking: Indonesia, Malaysia And Pakistan - Luqmanulhakim Luqmanulhakim; Ronald Rulindo; Saiful Anwar (LPPM ISNJ Bengkalis, 2021)
Following the 2008 financial crisis, the global economy will continue to experience shock in the years to come. Therefore, it is vital to conduct research that can anticipate the impact of fluctuations in financial stability. This research examines the stability of the Islamic banking system in Indonesia, Malaysia, and Pakistan, using Z-Score as a proxy variable for stability measurement and Markov Switching VAR for the method. The objectives are to identify which Islamic banking has better resilience in facing crisis and identify the economic variables that have a significant effect on the stability of Islamic banking. The results showed that the stability of Indonesian Islamic banking was more stable compared to Malaysia and Pakistan. The crisis periods determined from the method show that in 2019 all countries studied entered the beginning of the crisis period, which means the world conditions tend to re-enter the crisis, repeating the 2008 financial crisis.